Transforming the Religious Enthusiasm of Urban Muslims in the Choosing of Elementary-Level Education in Purwokerto, Indonesia - Muttaqin, Ahmad; Novikasari, Ifada (Islam Realitas: Journal of Islamic and Social Studies, 2024)
This paper aims to analyze religious enthusiasm that does not continue after the primary school period is over and instead shows contrasting situations. Urban Muslims in Purwokerto, Indonesia, show high religious enthusiasm when choosing primary schools for their children. The number of public elementary school students has declined in the last five years, while Madrasah Ibtida'iyyah has increased dramatically. This research is field-type with data sources from urban Muslims who choose Madrasah Ibtida'iyyah as a primary school choice for their children. The data were analyzed qualitatively using a sociological approach. The study found that the religious enthusiasm of urban Muslims is pragmatic. Their pragmatic nature is shown by the resistance of different social groups that give rise to covert conflicts. In addition, they form new communities that actively represent them in public spaces. This finding has implications for a change in the perspective of the phenomenon of religious enthusiasm from theological awareness to a new trend of community-based urban Muslim pragmatism. Further research recommended the representation of the new identity of Muslim communities in virtual public spaces. Tulisan ini bertujuan menganalisis antusiasme keagamaan orang tua yang tidak berlanjut pada jenjang pendidikan setelah Sekolah Dasar dan justru menunjukkan situasi yang kontras. Muslim perkotaan di Purwokerto, Indonesia, menunjukkan antusiasme agama yang tinggi dalam memilih Sekolah Dasar untuk anak-anak mereka. Jumlah siswa Sekolah Dasar Negeri mengalami penurunan dalam lima tahun terakhir, sebaliknya Madrasah Ibtida'iyyah meningkat secara drastis.. Penelitian ini berjenis lapangan dengan sumber data dari kelompok muslim perkotaan yang memilih Madrasah Ibtida'iyyah sebagai pilihan sekolah dasar untuk anak-anak mereka. Data dianalisis secara kualitatif dengan menggunakan pendekatan sosiologis. Studi ini menemukan bahwa antusiasme keagamaan muslim perkotaan bersifat pragmatis. Sifat pragmatis mereka ditunjukkan melalui perlawanan dan menimbulkan konflik terselubung. Selain itu, mereka membentuk komunitas baru yang secara aktif merepresentasikannya di ruang publik. Temuan ini berimplikasi pada perubahan perspektif fenomena antusiasme keagamaan dari kesadaran teologis ke kecenderungan baru pragmatisme. Penelitian lebih lanjut merekomendasikan representasi identitas baru komunitas muslim di ruang publik virtual.